Програмна система для контролю умови зберігання та перевезення вантажів у спеціфічних умовах оточуючого середовища «STORE&DELIVER» - Михневич, Д. К. (ХНУРЕ, 2022)
The purpose of this work is to create a software system for the storage and transportation of goods under certain conditions. Depending on the needs of the user, the system will provide the ability to select several modes: transportation mode and cargo storage mode with the ability to configure all the necessary parameters for each cargo, such as maximum and minimum temperature, humidity, lighting intensity during transportation or cargo storage. For the storage mode, it will be possible to order an additional security system. With the help of IoT device reading of all the necessary environmental parameters and the functioning of the security system will be ensured.
Keywords: програмна система; середовище